2004
DOI: 10.1210/jc.2003-031385
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phospholipase Isozymes by Nuclear Factor-κB in Human Gestational Tissuesin Vitro

Abstract: Phospholipid-derived mediators are implicated in the initiation and progression of human labor and delivery, particularly in relation to infection-induced preterm labor. We previously demonstrated that, in human intrauterine tissues, lipopolysaccharide (LPS)-stimulated nuclear factor-kappaB (NF-kappaB) DNA binding activity, and subsequent cytokine release can be suppressed by sulfasalazine (SASP) concentrations greater than 5 mM. The aim of this study was to elucidate the effect the SASP on secretory type II p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…In the present study, we found that pretreatment with helenalin or transfection with kinase inactive mutants of NIK and IKKb also attenuated TNF-a-induced NF-kB translocation and cPLA 2 expression, as well as PGE 2 production. These results suggested that TNF-a-stimulated NF-kB activation was mediated through NIK/IKKb pathway leading to cPLA 2 expression, consistent with the reports indicating that activation of NF-kB promotes cPLA 2 gene expression in several cell types (Lappas et al, 2004;Luo et al, 2006). Moreover, our results showed that pretreatment with helenalin, U0126, SB202190, or SP600125 significantly attenuated cPLA 2 luciferase gene activity stimulated by TNF-a, suggesting that activation of MAPKs and NF-kB pathways independently regulated cPLA 2 expression at a transcription level.…”
Section: Journal Of Cellular Physiology T N F -A R E G U L a T E S R supporting
confidence: 91%
“…In the present study, we found that pretreatment with helenalin or transfection with kinase inactive mutants of NIK and IKKb also attenuated TNF-a-induced NF-kB translocation and cPLA 2 expression, as well as PGE 2 production. These results suggested that TNF-a-stimulated NF-kB activation was mediated through NIK/IKKb pathway leading to cPLA 2 expression, consistent with the reports indicating that activation of NF-kB promotes cPLA 2 gene expression in several cell types (Lappas et al, 2004;Luo et al, 2006). Moreover, our results showed that pretreatment with helenalin, U0126, SB202190, or SP600125 significantly attenuated cPLA 2 luciferase gene activity stimulated by TNF-a, suggesting that activation of MAPKs and NF-kB pathways independently regulated cPLA 2 expression at a transcription level.…”
Section: Journal Of Cellular Physiology T N F -A R E G U L a T E S R supporting
confidence: 91%
“…Reactive oxygen species also culminate in phospholipase A 2 activation through transcription factor NF-kB (Lappas et al, 2004), as NF-kB can be activated by the stress of oxidants (Siebenlist et al, 1994) and oxalate exposure promotes rapid degradation of IkBa, an endogenous inhibitor of the NF-kB transcription factor (Jonassen et al, 2005). The inhibition of the lipid peroxidation (decreased MDA level) after post-treatment of plant extracts can be attributed to scavenging the ROS and indirect inhibition of phospholipase A 2 through inactivation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…ROS also culminate in phospholipase A 2 activation through transcription factor NF-κB (Lappas et al, 2004), as NF-κB can be activated by the stress of oxidants (Siebenlist et al, 1994) and oxalate exposure promotes rapid degradation of IκBα, an endogenous inhibitor of the NF-κB transcription factor (Jonassen et al, 2005). The inhibition of the lipid peroxidation (decreased MDA level) after post-treatment of BDE can be attributed to scavenging the ROS and indirect inhibition of phospholipase A 2 through inactivation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%